Can Mindful Eating Help Us When We Struggle With Eating? Mindful Eating Replaces Diets. - Gizem Köse (Türk Spor ve Egzersiz Dergisi)
Eating and weight related disorders are spreading widely all over the world. Individuals and health professionals are seeking effective and lifelong treatments for them. The purpose of this review was to summarize researches and evaluate the effectiveness of mindfulness and mindful eating on obesity, disordered eating and eating disorders. Practicing mindful eating has being used for emotional eating, binge eating, food cravings, and weight management. Past reviews interpreting the association between being mindful eating strategies and eating behaviors or attitudes may be showing us that mindful eating is the best way to deal with eating issues. Mindfulness and mindful eating related approaches can be used as a part of the treatment plans of obesity, disordered eatings and eating disorders due to the fact that these therapies are being worked as effectively practical.